Geopolymer concrete as sustainable material: A state of the art review. (1st November 2021) - Farooq, Furqan; Jin, Xin; Faisal Javed, Muhammad; Akbar, Arslan; Izhar Shah, Muhammad; Aslam, Fahid; Alyousef, Rayed
Graphical abstract: Highlights: A comprehensive review of geopolymer concrete. Constituents of geopolymer concrete in detail. Characterization of geopolymer concrete. Properties of geopolymer concrete. Environmental impact of geopolymer concrete. Abstract: The rise in population and improvement in the lifestyle of human beings has caused a rapid increase in energy demands for buildings in the present day. An upsurge in energy demand, lack of fossil fuels, and environmental issues provide a crucial motive to the development of sustainable and viable infrastructure. Geopolymer (GP) composite free from cement, made from various waste materials with a high amount of Al2 SiO3 and Na2 SiO3 /NaOH (alkali-activated silica) is evolving as an eminent material for sustainability purposes. They are also preferred due to the lesser emission of greenhouse gases as compared to ordinary Portland cement (OPC). This paper aims at presenting a sustainable domain and state of the art review of GP composite. The properties of composites made from various geopolymeric waste binders are presented. Besides, the microstructure and chemical characterization of GP composites are also discussed. The durability of GP composite is also highlighted considering its deterioration in various aggressive environments. In the end, a global warming potential (GWP) assessment was conducted and the practical applications of GP composites in the building industry are also provided.